Reconstruction of Physics Concepts from Indigenous Knowledge in the Sasak Arak-Arakan Besunat Tradition Using Praje to Support SDG 4 (Quality Education) - Rabiatun Adawiah; Salwa Nur Sapiatun Nakjah; Ni Ketut Anggriani; Surajuddin; Gito Hadiprayitno (Postgraduate, University of Mataram, 2026)
This study aims to reconstruct physics concepts embedded in the Sasak Arak-arakan besunat tradition using praje into formal physics knowledge as a contextual ethnoscience-based learning resource supporting SDG 4 (Quality Education). The study employed a qualitative descriptive method with an ethnographic-ethnoscience approach. Data was collected through interviews, observations and documentation and scientific verification involving traditional leaders, praje craftsmen and parents in East Lombok. The data were analyzed through data reduction, identification of indigenous knowledge, scientific verification and reconstruction into school science concepts. The findings show that the tradition contains several contextual physics concepts, including Newton’s Laws, center of mass and dynamic equilibrium in maintaining praje stability, work and changes in potential and kinetic energy during lifting activities, impulse and momentum in drumstick collisions on gendang beleq, sound resonance in traditional musical instruments and uniform as well as accelerated motion during the procession. These concepts are empirically applied in community practices and can be scientifically reconstructed into formal physics learning concepts. The integration of indigenous knowledge has the potential to enhance students’ conceptual understanding and cultural literacy through contextual learning experiences.